ICT Security Tools and Techniques among Higher Education Institutions: A Critical Review - Nuñez, Miko; Palmer, Xavier-Lewis; Potter, Lucas; Aliac, Chris Jordan; Velasco, Lemuel Clark (International Journal of Emerging Technologies in Learning (iJET), 2023)
Higher education institutions (HEIs) are increasingly relying on digital technologies for classroom and organizational management, but this puts them at higher risk for information and communication (ICT security attacks. Recent studies show that HEIs have experienced more security breaches in ICT security composed of both cybersecurity an information security. A literature review was conducted to identify common ICT security practices in HEIs over the last decade. 11 journal articles were profiled and analyzed, revealing threats to HEIs’ security and protective measures in terms of organizational security, technological security, physical security, and standards and frameworks. Security tools and techniques were grouped into categories with specific ways to protect ICT security. HEIs also implement general security standards and guidelines, such as the ISO 27000-series and Center for Internet Security (CIS) controls, in their framework. Through synthesis and analysis of ICT security tools and techniques among HEIs, this critical review hopes to provide research directions on IT governance that academic and technical administrators can further explore to secure their information resources.